Selfo: A class of self-organizing connection games - Vico-Vela, Francisco José (My University, 2007)
Selfo is defined as a class of abstract strategy board games subscribed to the category of connection games. Its name derives from the phenomenon of self-organization (i.e. the increase in a system’s organization without external guidance), since during the game the sets of pieces might flow in a coordinated way as they step on the board. Despite its very simple definition (“group all your pieces by moving in turns to adjacent cells”) complex self-organization processes takes place under concrete circumstances (a balanced distribution of pieces and similar levels of expertise in the players), and are the result of abrupt and deep changes in the tactics. Since a big number of variants have been found to meet the conditions for self-organization, the particular values given to the traditional parameters that define a game (i.e., board tiling, size and initial position, or number of pieces and players) are not so relevant. The Selfo class of connection games is defined, instead, by the interrelations among parameters in order to favor selforganization.
Keywords: Juegos; Board game; Connection game